Lisa Jakelski, Making New Music in Cold War Poland. The Warsaw Autumn Festival, 1956–1968, Oakland 2017 - Beata Bolesławska-Lewandowska (Muzyka, 2018)
Recenzja książki: Lisa Jakelski, Making New Music in Cold War Poland. The Warsaw Autumn Festival, 1956–1968, Oakland 2017